Lithium secondary battery

By using lithium metal oxide cathodes modified with doped elements and ceramic-coated separators in lithium secondary batteries, the problems of fire risk, insufficient lifespan, and insufficient power in lithium secondary batteries when damaged or punctured by external forces have been solved, achieving higher stability and safety.

CN120834256APending Publication Date: 2025-10-24SK ON CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510487429.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-19
Filing Date
2025-04-18
Publication Date
2025-10-24

AI Technical Summary

Technical Problem

Existing lithium secondary batteries pose a fire risk when damaged or punctured by external forces, and have insufficient lifespan and power characteristics.

Method used

The cathode is modified with doped elements and the separator is ceramic coated with elements such as Al, Ti, and Zr. The ratio of the thickness of the ceramic coating to the total thickness of the separator is 0.13 to 0.44, which improves the structural stability of the cathode. The separator consists of a substrate film and a ceramic coating, which enhances the puncture resistance.

Benefits of technology

It improves the lifespan, power characteristics, and stability of lithium secondary batteries, and reduces the risk of fire caused by external damage or puncture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120834256A_ABST
    Figure CN120834256A_ABST
Patent Text Reader

Abstract

A lithium secondary battery according to an embodiment of the present invention may include: a positive electrode including a positive electrode active material layer including a positive electrode active material including a lithium metal oxide in the form of secondary particles in which a plurality of primary particles are aggregated, and in which a doping element is doped; and the negative electrode is arranged opposite to the positive electrode. Further, the lithium secondary battery may include a separator disposed between the positive electrode and the negative electrode, and including a base material film and a ceramic coating layer formed on at least one surface of the base material film. The aspect ratio of the primary particles may be 1.4 to 7.0, and the ratio of the thickness of the ceramic coating to the thickness of the separator may be 0.13 to 0.44.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a lithium secondary battery. BACKGROUND

[0002] A secondary battery is a battery that can be repeatedly charged and discharged, and as the information communication and display industries have developed, secondary batteries are widely used as power sources for portable electronic communication devices such as camcorders, mobile phones, notebook computers, etc. In addition, in recent years, a battery pack including a secondary battery is being developed and used as a power source for environmentally friendly vehicles such as hybrid electric vehicles.

[0003] Among secondary batteries, for example, a lithium secondary battery has a high operating voltage and an energy density per unit weight, and is advantageous in terms of charging speed and light weight, and thus is actively being researched and developed.

[0004] For example, a lithium secondary battery can include an electrode assembly including a cathode, an anode, and a separator (separation film), and an electrolyte impregnating the electrode assembly. The lithium secondary battery can further include an outer material, for example, an outer material in the form of a pouch, which accommodates the electrode assembly and the electrolyte.

[0005] A secondary battery including an electrolyte can have high capacity characteristics and electrical characteristics due to the high reactivity of the electrolyte. However, when a secondary battery including an electrolyte is damaged or punctured due to an external force, a stability problem such as a fire risk can occur due to the high reactivity of the electrolyte. SUMMARY

[0006] (I) Technical Problem to be Solved

[0007] One technical problem of the present application is to provide a lithium secondary battery having improved lifespan characteristics, power characteristics, and stability.

[0008] (II) Technical Solution

[0009] A lithium secondary battery according to an exemplary embodiment can include a cathode including a lithium metal oxide, the lithium metal oxide including a secondary particle in which a plurality of primary particles are aggregated, and the lithium metal oxide being doped with a doping element, and an anode disposed opposite the cathode. In addition, the lithium secondary battery can include a separator disposed between the cathode and the anode, and the separator including a base film and a ceramic coating layer formed on at least one side of the base film. An aspect ratio of the primary particles can be 1.4 to 7.0, and a ratio of a thickness of the ceramic coating layer to a total thickness of the separator can be 0.13 to 0.44.

[0010] In some embodiments, the aspect ratio can be 2.5 to 5.5.

[0011] In some embodiments, the lithium metal oxide can contain nickel, and the mole fraction of nickel in the total moles of all elements other than lithium and oxygen in the lithium metal oxide can be 0.5 or more and less than 1.

[0012] In some embodiments, the mole fraction of the nickel in the total moles of all elements other than lithium and oxygen in the lithium metal oxide can be 0.6 to 0.94.

[0013] In some embodiments, the doping element can contain at least one selected from the group consisting of Al, Ti, Zr, Ba, Sr, W, Nb, Y, Mg, V, Ta, Mo, La, and B.

[0014] In some embodiments, the doping element can contain at least one selected from the group consisting of Al, Ti, Zr, W, V, La, and B.

[0015] In some embodiments, the doping element can contain two or more different doping elements.

[0016] In some embodiments, the content of the doping element can be 300 ppm to 15000 ppm with respect to the total weight of the lithium metal oxide.

[0017] In some embodiments, the content of the doping element can be 2500 ppm to 12000 ppm with respect to the total weight of the lithium metal oxide.

[0018] In some embodiments, the ratio of the thickness of the ceramic coating to the total thickness of the separator can be 0.17 to 0.33.

[0019] In some embodiments, the total thickness of the separator can be 9 μm to 18 μm.

[0020] In some embodiments, the thickness of the ceramic coating can be 2 μm to 6 μm.

[0021] In some embodiments, the ceramic coating can contain a ceramic material and a binder for a coating of a separator.

[0022] In some embodiments, the ceramic material can contain at least one selected from the group consisting of alumina, titania, barium titanate, magnesium oxide, zirconia, zinc oxide, boehmite, aluminum hydroxide, magnesium hydroxide, and silica.

[0023] (III) ADVANTAGEOUS EFFECTS

[0024] The lithium secondary battery according to exemplary embodiments of the present application can have improved lifespan characteristics and capacity characteristics.

[0025] The lithium secondary battery according to exemplary embodiments can use a lithium metal oxide doped with a doping element as a positive electrode active material. By the doping element, structural deterioration of the positive electrode active material due to charging / discharging can be suppressed. Accordingly, reduction in lifespan characteristics and capacity characteristics due to damage of the positive electrode active material can be suppressed.

[0026] Further, the separator includes a coating layer, and thus stability can be improved even if damage or puncture due to external force occurs. For example, even if the separator is punctured, occurrence of fire or the like can be suppressed by the coating layer.

[0027] The lithium secondary battery of the present application can be widely applied to electric vehicles, battery charging stations, other green technology fields using batteries such as solar power generation, wind power generation, etc. The lithium secondary battery of the present application can be used in eco-friendly electric vehicles (Electric Vehicle) and hybrid vehicles, etc. by suppressing emission of atmospheric pollution and greenhouse gases to prevent climate change. BRIEF DESCRIPTION OF DRAWINGS

[0028] Figure 1 and Figure 2 FIGS. 1 and 2 are schematic plan and cross-sectional views, respectively, illustrating a lithium secondary battery according to exemplary embodiments.

[0029] Figures 3 to 8 FIGS. 3 and 4 are images of a cross-section of a positive electrode active material particle according to exemplary embodiments, measured using a Scanning Electron Microscope (SEM).

[0030] Figure 9 FIG. 5 is a schematic cross-sectional view illustrating a separator according to exemplary embodiments.

[0031] REFERENCE NUMERALS:

[0032] 100: positive electrode; 105: positive electrode current collector

[0033] 107: positive electrode lead; 110: positive electrode active material layer

[0034] 120: negative electrode active material layer; 125: negative electrode current collector

[0035] 127: negative electrode lead; 130: negative electrode

[0036] 140: separator; 145: base film

[0037] 147: ceramic coating layer; 150: electrode assembly

[0038] 160: case DETAILED DESCRIPTION

[0039] According to an exemplary embodiment of the present application, there is provided a lithium secondary battery including: a positive electrode including a positive electrode active material layer containing a lithium metal oxide in a form of secondary particles formed by aggregation of a plurality of primary particles; a negative electrode disposed opposite to the positive electrode; and a separator disposed between the positive electrode and the negative electrode.

[0040] Hereinafter, the present application will be described in detail with reference to the accompanying drawings. However, this is merely an exemplary description, and the present application is not limited to the specific embodiments described by way of example.

[0041] Hereinafter, in the present application, unless specifically defined otherwise, when a portion such as a layer, a film, a thin film, a region, a plate, etc. is described as being "on" another portion, this can include not only a case where it is "directly on" the other portion, but also a case where another portion is interposed therebetween.

[0042] Figure 1 and Figure 2 are a schematic plan view and a schematic cross-sectional view, respectively, showing a lithium secondary battery according to an exemplary embodiment. For example, Figure 2 is a cross-sectional view taken along line I-I' of Figure 1 .

[0043] Referring to Figure 1 and Figure 2 , the lithium secondary battery can include a positive electrode 100, a negative electrode 130 disposed opposite to the positive electrode 100, and a separator 140 disposed between the positive electrode 100 and the negative electrode 130.

[0044] According to an exemplary embodiment, the positive electrode 100 can include a positive electrode current collector 105 and a positive electrode active material layer 110 disposed on at least one face of the positive electrode current collector 105. The positive electrode 100 can contain a lithium metal oxide including a plurality of primary particles aggregated in a form of secondary particles, and the lithium metal oxide can be doped with a doping element.

[0045] The positive electrode current collector 105 can include stainless steel, nickel, aluminum, titanium, or an alloy thereof. The positive electrode current collector 105 can further include aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver. The positive electrode current collector 105 is not limited thereto, but for example, the thickness of the positive electrode current collector 105 can be 10 μm to 50 μm.

[0046] According to an exemplary embodiment, the positive electrode active material layer 110 can include a positive electrode active material. The positive electrode active material can include a compound in which lithium ions can be reversibly intercalated and deintercalated.

[0047] According to an exemplary embodiment, the positive electrode active material can include a lithium metal oxide in the form of secondary particles in which a plurality of primary particles are aggregated.

[0048] According to an exemplary embodiment, the aspect ratio of the primary particle can be 1.4 to 7.0.

[0049] When the aspect ratio of the primary particle is less than 1.4, the primary particle can not be stably aggregated. For example, due to repeated charging / discharging, a secondary particle can generate a crack, which can increase the generation of a gap or a pore inside a secondary particle in which a plurality of primary particles are aggregated, and thus can reduce structural stability. Accordingly, the life characteristics of the positive electrode active material can be reduced.

[0050] The primary particle can be distinguished from the secondary particle in terms of morphology. For example, the secondary particle can refer to a particle in which a plurality of primary particles are aggregated and substantially regarded or observed as one particle. For example, in the case of the secondary particle, the boundary of the primary particle can be observed in a scanning electron microscope (SEM) cross-sectional image.

[0051] When the aspect ratio of the primary particle exceeds 7.0, the length of the long axis, which is a movement path of lithium ions, can become excessively long, and thus the power characteristics can be reduced.

[0052] The term "aspect ratio" used in the present specification refers to the ratio of the length of the long axis to the length of the short axis of the primary particle. For example, the "aspect ratio" refers to the ratio of the length of the longest straight line to the length of the shortest straight line in a straight line that passes through the center of a cross-section of the primary particle and transversely crosses the cross-section of the primary particle. For example, the closer the aspect ratio is to 1, the more spherical the particle is, and the greater the aspect ratio is, the more rod type the particle is.

[0053] Figures 3 to 8 is an image of a cross-section of a positive electrode active material particle according to an exemplary embodiment, which is measured using a scanning electron microscope (SEM).

[0054] Specifically, Figure 3 and Figure 4 are images of a cross-section of any one of positive electrode active material particles of a secondary particle structure in which primary particles having an aspect ratio of 1.42 are aggregated, which are measured using an SEM. Figure 5 andFigure 6 are images of a cross section of any of the positive active material particles of a secondary particle structure in which primary particles having an aspect ratio of 2.58 are aggregated, measured using SEM. Figure 7 and Figure 8 are images of a cross section of any of the positive active material particles of a secondary particle structure in which primary particles having an aspect ratio of 6.51 are aggregated, measured using SEM.

[0055] Referring to Figures 3 to 8 It can be seen that when the primary particles have an aspect ratio of 1.42 to 6.51, the primary particles are stably aggregated to form secondary particles.

[0056] For example, the primary particles can have an aspect ratio of 1.42 to 7.0 or 1.5 to 7.0. Within the above ranges, the primary particles can be aggregated and stably form secondary particles. Thus, collapse of the secondary particle morphology due to repeated charging / discharging of the positive active material can be inhibited, and thus both the life characteristics and the power characteristics can be improved.

[0057] In some embodiments, the primary particles can have an aspect ratio of 1.53 to 6.51, 2.0 to 6.51, 2.5 to 6.51, 2.5 to 6.0, 2.5 to 5.5, 2.58 to 5.5, or 2.58 to 5.02. Within the above ranges, the life characteristics and the power characteristics can be further improved.

[0058] In exemplary embodiments, the positive active material can include a lithium metal oxide. For example, the primary particles can be a lithium metal oxide, and the secondary particles formed by aggregation of the primary particles can also be a lithium metal oxide.

[0059] In some embodiments, the lithium metal oxide can have an average particle diameter (D 50 ) of 3 μm to 25 μm, 5 μm to 25 μm, or 5 μm to 20 μm. Within the above ranges, insertion and extraction of lithium ions can be more easily achieved.

[0060] The term "average particle diameter (D 50 )" used in the present invention can mean a particle diameter at which a volume fraction is 50% in a particle size distribution on a volume basis of the lithium metal oxide.

[0061] In some embodiments, the positive active material or the lithium metal oxide can include nickel. For example, the positive active material or the lithium metal oxide can include a layered structure or a crystal structure represented by the following Chemical Formula 1.

[0062] [Chemical Formula 1]

[0063] Li x Ni a M b O 2+z

[0064] In Chemical Formula 1, 0.8≤x≤1.2, 0.5≤a≤1, 0≤b≤0.5, −0.2≤z≤0.2, and a+b=1. M may include Co, Mn, and / or Al.

[0065] The chemical structure represented by Chemical Formula 1 represents the bonding relationship contained in the layered structure or crystal structure of the positive active material, and does not exclude other additional elements. For example, M may include Co and / or Mn, and Co and / or Mn may be provided together with Ni as the main active element (main active element) of the positive active material. Chemical Formula 1 is provided to represent the bonding relationship of the main active elements, and it should be understood that Chemical Formula 1 is a formula including the introduction and substitution of additional elements.

[0066] In one embodiment, in addition to the main active element, an auxiliary element for enhancing the stability of the positive electrode active material or the layered structure / crystal structure may be further included. The auxiliary element may be mixed into the layered structure / crystal structure and form a bond, and it should be understood that this situation is also included in the chemical structure represented by Chemical Formula 1.

[0067] The auxiliary element may include, for example, at least one selected from Na, Mg, Ca, Y, Ti, Hf, V, Nb, Ta, Cr, Mo, W, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Sr, Ba, Ra, P, La, or Zr. The auxiliary element may function as an auxiliary active element that contributes to the power activity of the positive electrode active material together with Co or Mn, such as Al.

[0068] For example, the positive active material or the lithium metal oxide may include a layered structure or a crystal structure represented by the following Chemical Formula 1-1.

[0069] [Chemical Formula 1-1]

[0070] Li x Ni a M1 b1 M2 b2 O 2+z

[0071] In Chemical Formula 1-1, M1 can include Co, Mn, and / or Al. M2 can include the above-mentioned auxiliary elements. In Chemical Formula 1-1, it can be 0.8≤x≤1.2, 0.5≤a≤1, 0≤b1+b2≤0.5, -0.2≤z≤0.2, a+b1+b2=1.

[0072] The positive active material can include a nickel cobalt manganese (NCM)-based lithium oxide. In this case, an NCM-based lithium oxide having an increased content of nickel can be used.

[0073] Ni can be provided as a transition metal related to the power and capacity of a lithium secondary battery. Accordingly, as described above, by using a high content (High-Ni) composition for the positive active material, a high-capacity positive electrode and a high-capacity lithium secondary battery can be provided.

[0074] However, as the content of Ni increases, the long-term storage stability and life stability of the positive electrode or secondary battery can be relatively reduced, and the side reaction with the electrolyte can also increase. However, according to the exemplary embodiments, the conductivity can be maintained by including Co, and at the same time, the life stability and capacity retention characteristics can be improved by Mn.

[0075] In some embodiments, the mole fraction of the nickel (e.g., the mole fraction of the nickel in the total moles of nickel, cobalt, and manganese) in the total moles of all elements other than lithium and oxygen in the lithium metal oxide can be 0.5 or more and less than 1, 0.5 to 0.99, 0.6 to 0.99, or 0.6 to 0.98. Within the above ranges, the power characteristics and life characteristics of the positive active material can be improved at the same time. For example, the capacity characteristics can be improved by the nickel element, and at the same time, the structural stability can be improved by the remaining elements other than nickel. For example, by increasing the content of the nickel element, the capacity characteristics can be improved, and thus the amount of use of the lithium metal oxide can be reduced. Accordingly, the thickness of the electrode (e.g., the positive electrode) can be reduced, and thus the power characteristics can be improved.

[0076] In one embodiment, the mole fraction of the nickel (e.g., the mole fraction of the nickel in the total moles of nickel, cobalt, and manganese) in the total moles of all elements other than lithium and oxygen in the lithium metal oxide can be 0.6 to 0.95, 0.6 to 0.94, 0.6 to 0.92, 0.7 to 0.92, 0.7 to 0.9, or 0.75 to 0.9. Within the above ranges, the power characteristics and life characteristics of the positive active material can be further improved.

[0077] In an exemplary embodiment, the positive electrode active material (e.g., the lithium metal oxide) can further include a coating element or a doping element. In one embodiment, the coating element or the doping element can penetrate into the inside of the primary particles and be located in the inside of the primary particles. In one embodiment, the coating element or the doping element can be formed on the surface of the primary particles (e.g., between the primary particles). In one embodiment, the coating element or the doping element can be located on the surface of the secondary particles in which the primary particles are aggregated.

[0078] In some embodiments, the doping element or the coating element can include at least one selected from Al, Ti, Zr, Ba, Sr, W, Nb, Y, Mg, V, Ta, Mo, La, and B. Accordingly, by the doping element, the structural stability of the primary particles or the secondary particles in which the primary particles are aggregated can be improved, and thus the life characteristics can be improved. In addition, the conductivity of the positive electrode active material can be improved, and thus the power characteristics can be improved.

[0079] In one embodiment, the doping element or the coating element can include at least one selected from Al, Ti, Zr, W, V, La, and B. Accordingly, the life characteristics and the power characteristics of the positive electrode active material can be further improved.

[0080] In some embodiments, the doping element or the coating element can use a combination of two or more different doping elements or coating elements. For example, the doping element or the coating element can use a combination of Al and Y, Zr and Mo, Sr and W, Nb and Ti, Mg and B, Ta and Ba, or La and V. Accordingly, the life characteristics and the power characteristics of the positive electrode active material can be further improved.

[0081] In one embodiment, the doping element or the coating element can use a combination of three elements. For example, the doping element or the coating element can use a combination of Ti, Sr, and Y or Al, Zr, and W. Accordingly, the life characteristics and the power characteristics of the positive electrode active material can be further improved.

[0082] In some embodiments, the content of the doping element or the coating element can be 300 ppm to 15,000 ppm, 1,000 ppm to 14,000 ppm, or 2,000 ppm to 14,000 ppm, based on the total weight of the positive electrode active material (e.g., the lithium metal oxide). Within the above content range, the doping element or the coating element can exist in a form that maintains an appropriate interval. Accordingly, the side reaction due to the doping element or the coating element can be suppressed, and thus the conductivity of the positive electrode active material can be improved. Accordingly, the life characteristics and the power characteristics can be improved.

[0083] In one embodiment, the content of the doping element or the coating element can be 2500 ppm to 12000 ppm, 2500 ppm to 10000 ppm, 2500 ppm to 8000 ppm, 2500 ppm to 6000 ppm, 2500 ppm to 4500 ppm, or 3500 ppm to 4500 ppm of the total weight of the positive electrode active material (e.g., lithium metal oxide). Within the above content range, the power characteristics and the life characteristics of the positive electrode active material can be further improved.

[0084] In some embodiments, the positive electrode active material can further include a lithium cobalt oxide-based active material, a lithium manganese oxide-based active material, a lithium nickel oxide-based active material, a lithium metal phosphate-based active material (e.g., LiFePO4), while including the lithium metal oxide.

[0085] In some embodiments, the positive electrode active material can further include, for example, a Mn-rich-based active material having a chemical structure or a crystal structure represented by the following Chemical Formula 2, a Li-rich Layered Oxide (LLO) / Over Lithiated Oxide (OLO)-based active material, a Co-less-based active material, while including the lithium metal oxide.

[0086] [Chemical Formula 2]

[0087] p[Li2MnO3]·(1-p)[Li q JO2]

[0088] In Chemical Formula 2, 0 < p < 1, 0.9 ≤ q ≤ 1.2, and J can include at least one element among Mn, Ni, Co, Fe, Cr, V, Cu, Zn, Ti, Al, Mg, and B.

[0089] For example, the above-described positive electrode active material can be mixed in a solvent to prepare a positive electrode slurry. The positive electrode slurry can be coated on the positive electrode current collector 105, followed by drying and calendering to prepare the positive electrode active material layer 110. The coating process can be performed by a method such as gravure coating, slot-die coating, multi-layer simultaneous die coating, stamping, doctor blade coating, dip coating, bar coating, casting, etc., and is not limited thereto. The positive electrode active material layer 110 can further include a binder, and can optionally further include a conductive material, a thickening agent, etc.

[0090] As non-limiting examples of solvents used when preparing the positive electrode active material layer 110, N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, N,N-dimethylaminopropylamine, oxirane, tetrahydrofuran, and the like can be listed.

[0091] The binder can include polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-co-hexafluoropropylene), polyacrylonitrile, polymethylmethacrylate, acrylonitrile butadiene rubber (NBR), poly(butadiene) rubber (BR), styrene-butadiene rubber (SBR), and the like. In one embodiment, a PVDF-based binder can be used as a positive electrode binder.

[0092] The conductive material can be added to enhance the conductivity of the positive electrode active material layer 110 and / or the mobility of lithium ions or electrons. For example, the conductive material can include carbon-based conductive materials such as graphite, carbon black, acetylene black, ketjen black, graphene, carbon nanotubes, Vapor-Grown Carbon Fiber (VGCF), carbon fibers, and / or metal-based conductive materials including perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, LaSrMnO3, and the like, but is not limited thereto.

[0093] The positive electrode active material layer 110 can further include a thickening agent and / or a dispersing agent, and the like. For example, the positive electrode active material layer 110 can include a thickening agent such as carboxy methyl cellulose (CMC).

[0094] The negative electrode 130 can include a negative electrode current collector 125 and a negative electrode active material layer 120 formed on at least one side of the negative electrode current collector 125.

[0095] As non-limiting examples of the negative electrode current collector 125, a copper foil, a nickel foil, a stainless steel foil, a titanium foil, a foam nickel, a foam copper, a polymer substrate coated with an electrically conductive metal, and the like can be listed. The negative electrode current collector 125 is not limited thereto, but for example, the thickness of the negative electrode current collector 125 can be 10 μm to 50 μm.

[0096] The negative electrode active material layer 120 can include a negative electrode active material. The negative electrode active material can use a substance that can intercalate and deintercalate lithium ions. For example, the negative electrode active material can include carbon-based materials such as crystalline carbon, amorphous carbon, carbon composite, carbon fiber, and the like; lithium metal; lithium alloy; silicon (Si)-containing substance or tin (Sn)-containing substance, and the like.

[0097] The amorphous carbon can include, for example, mesocarbon microbead (MCMB), mesophase pitch-based carbon fiber (MPCF), and the like.

[0098] As examples of the crystalline carbon, graphite-based carbons such as natural graphite, artificial graphite, graphitized coke, graphitized MCMB, graphitized MPCF, and the like can be listed.

[0099] The lithium metal can include pure lithium metal or lithium metal formed with a protective layer for suppressing dendrite growth, and the like. In one embodiment, a layer containing lithium metal deposited or coated on the negative electrode current collector 125 can be used as the negative electrode active material layer 120. In one embodiment, a lithium thin film layer can be used as the negative electrode active material layer 120.

[0100] As elements included in the lithium alloy, aluminum, zinc, bismuth, cadmium, antimony, silicon, lead, tin, gallium, indium, and the like can be listed.

[0101] The silicon-containing substance can provide further increased capacity characteristics. The silicon-containing substance can include Si, SiO x (0 < x < 2), SiO x (0 < x < 2) doped with a metal, silicon-carbon composite, and the like. The metal can include lithium and / or magnesium, SiO x (0 < x < 2) doped with a metal can include a metal silicate.

[0102] For example, the negative active material can be mixed in a solvent to prepare a negative electrode slurry. The negative electrode slurry can be coated / deposited on the negative electrode current collector 125, followed by drying and calendering to prepare the negative active material layer 120. The coating process can be performed by a method such as gravure coating, slot-die coating, multi-layer simultaneous die coating, stamping, blade coating, dip coating, bar coating, casting, and the like, and is not limited thereto. The negative active material layer 120 can further include a binder, and can optionally further include a conductive material, a thickening agent, and the like.

[0103] The solvent for the negative active material layer 120 can include, for example, water, pure water, deionized water, distilled water, ethanol, isopropyl alcohol, methanol, acetone, n-propanol, t-butanol, and the like.

[0104] As the binder, conductive material, and thickening agent, the above-described substances that can be used in the manufacture of the positive electrode can be used.

[0105] In some embodiments, the negative electrode binder can include, for example, a styrene butadiene rubber (SBR)-based binder, carboxymethyl cellulose (CMC), a polyacrylic acid-based binder, a poly(3,4-ethylenedioxythiophene) (PEDOT)-based binder, and the like.

[0106] According to an exemplary embodiment, a separator 140 can be disposed between the positive electrode 100 and the negative electrode 130. The separator 140 can be disposed to prevent a short circuit between the positive electrode and the negative electrode and to generate a flow of ions.

[0107] Figure 9 FIG. 1 is a schematic cross-sectional view illustrating a battery according to an exemplary embodiment.

[0108] Referring to FIG. 1, Figure 9 The separator 140 can include a base film 145 and a ceramic coating layer 147 formed on at least one side of the base film.

[0109] In some embodiments, the ceramic coating layer 147 can be disposed on at least one of the two sides of the separator 140 that are in contact with the positive electrode 100 and the negative electrode 130. For example, the ceramic coating layer 147 disposed on the base film 145 can be in contact with at least one of the side of the positive electrode 100 and the side of the negative electrode 130.

[0110] For example, the ceramic coating layer 147 disposed on the base film 145 can be in contact with the side of the positive electrode 100. For example, the ceramic coating layer 147 disposed on the base film 145 can be in contact with the side of the negative electrode 130. For example, the ceramic coating layers 147 disposed on the two sides of the base film 145 can be in contact with the side of the positive electrode 100 and the side of the negative electrode 130, respectively.

[0111] According to an exemplary embodiment, the ratio of the thickness of the ceramic coating layer 147 to the total thickness of the separator 140 can be 0.13 to 0.44.

[0112] When the ratio of the thickness of the ceramic coating layer 147 to the thickness of the separator 140 is less than 0.13, the ceramic coating layer 147 can not stably protect the base film 145. Thus, when damage or puncture occurs due to an external force, the substances contained in the positive electrode 100 and the substances contained in the negative electrode 130 can move through the damaged or punctured separator 140 to cause a fire or the like, thereby possibly reducing stability.

[0113] When the ratio of the thickness of the ceramic coating layer 147 to the total thickness of the separator 140 exceeds 0.44, since the ceramic coating layer 147 is thick, ions can not move smoothly, thereby possibly reducing power characteristics.

[0114] By maintaining the ratio of the thickness of the ceramic coating layer 147 to the total thickness of the separator 140 in the range of 0.13 to 0.44, it is possible to improve safety while improving capacity characteristics and power characteristics.

[0115] In some embodiments, the ratio of the thickness of the ceramic coating layer 147 to the total thickness of the separator 140 can be 0.13 to 0.42, 0.13 to 0.40, 0.17 to 0.40, or 0.17 to 0.33. In the above ranges, puncture stability can be improved, and capacity characteristics and power characteristics can be further improved.

[0116] In one embodiment, the ratio of the thickness of the ceramic coating layer 147 to the total thickness of the separator 140 can be 0.20 to 0.33, 0.22 to 0.33, or 0.25 to 0.33. In the above ranges, capacity characteristics and power characteristics can be further improved.

[0117] In some embodiments, the total thickness of the separator 140 can be 9 μm to 18 μm, 9 μm to 15 μm, 10 μm to 15 μm, or 12 μm to 15 μm. In the above ranges, substances between the positive electrode 100 and the negative electrode 130 can be stably separated from each other, and ion flow can be stably generated.

[0118] In some embodiments, the thickness of the base film 145 can be 3 μm to 16 μm, 4 μm to 13 μm, 6 μm to 13 μm, or 8 μm to 12 μm. In the above ranges, movement of ions through the separator 140 can proceed smoothly.

[0119] In some embodiments, the ceramic coating layer 147 can have a thickness of 2 to 6 μm, 2 to 5 μm, 2 to 4 μm, or 3 to 4 μm. In the above range, the base film 145 can be protected even if damage occurs due to external force. Thus, the stability of the separator 140 can be improved.

[0120] The thickness of the ceramic coating layer 147 can refer to the total thickness of the ceramic coating layer 147. For example, when the ceramic coating layer 147 is formed on only one side of the base film 145, the thickness of the ceramic coating layer 147 can refer to the thickness of one ceramic coating layer 147. For example, when the ceramic coating layer 147 is formed on both sides of the base film 145, the thickness of the ceramic coating layer 147 can refer to the sum of the thicknesses of the ceramic coating layers 147 formed on both sides.

[0121] In some embodiments, the separator 140 can include a ceramic material and an adhesive for a coating layer of a separator. For example, the ceramic material can be fixed by the adhesive for the coating layer of the separator, and thus the ceramic coating layer 147 can be provided on the base film 145.

[0122] The term "ceramic material" used in the present application can refer to a substance including a ceramic. For example, both a case where a ceramic is used alone and a case where a ceramic is used in combination with other elements or compounds can be included.

[0123] In some embodiments, the adhesive for a coating layer of a separator can include a polyvinylidene fluoride (PVDF), a vinylidene-hexafluoropropylene copolymer (poly(vinylidene fluoride-co-hexafluoropropylene) copolymer), a polyvinylidene fluoride-trichloroethylene (poly(vinylidene fluoride-co-trichloroethylene) copolymer) and the like PVDF-based adhesive, and a polymethyl methacrylate and the like acrylate-based adhesive.

[0124] For example, the adhesive for a coating layer of a separator can also include at least one selected from the group consisting of a polyacrylate, a polybenzoate, a polyvinylpyrrolidone, a polystyrene, a polymethyl methacrylate, a polybutyl acrylate, a polyvinylidene fluoride, and a copolymer thereof.

[0125] For example, the adhesive for the coating layer of the diaphragm can also include a rubber-based adhesive such as nitrile rubber (NBR), polybutadiene rubber (BR), styrene butadiene rubber (SBR), polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer (poly(ethylene-co-vinyl acetate)), polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylpullulan, cyanoethylpolyvinylalcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan, carboxyl methylcellulose, polyvinylalcohol, or the like. These can be used alone or two or more kinds thereof can be used in mixture.

[0126] In some embodiments, the ceramic material can include alumina (Al2O3), titanium oxide (TiO), barium titanate (BaTiO3), magnesium oxide (MgO), zirconia (ZrO2), zinc oxide (ZnO), boehmite (AlO(OH)), aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), silica (SiO2), titanium dioxide (TiO2), calcium oxide (CaO), yttrium oxide (Y2O3), nickel oxide (NiO), silicon carbide (SiC), lead titanate (PbTiO3), lead zirconate titanate (PZT), lead magnesium niobate-lead titanate (PMN-PT), hafnium oxide (HfO2), strontium titanate (SrTiO3), tin dioxide (SnO2), cerium oxide (CeO2), or the like. These can be used alone or in combination with two or more.

[0127] In one embodiment, the ceramic material can include at least one selected from alumina (Al2O3), titanium oxide (TiO), barium titanate (BaTiO3), magnesium oxide (MgO), zirconia (ZrO2), zinc oxide (ZnO), boehmite (AlO(OH)), aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), and silica (SiO2). Accordingly, the stability of suppressing ignition by the ceramic coating 147 can be further improved.

[0128] In some embodiments, the content of the ceramic material can be 80 to 99% by weight, 85 to 99% by weight, 90 to 99% by weight, 92 to 98% by weight, or 94 to 98% by weight, in the total weight of the ceramic coating 147. Within the above range, the stability of the separator 140 can be improved by the ceramic material.

[0129] In some embodiments, the content of the binder of the coating for the separator can be 1 to 20% by weight, 1 to 15% by weight, 1 to 10% by weight, 2 to 8% by weight, or 2 to 6% by weight in the total weight of the ceramic coating 147. Within the above ranges, the ceramic coating 147 can be stably fixed on the base film 145 by the binder of the coating for the separator.

[0130] In some embodiments, the base film 145 can include a porous polymer film or a porous nonwoven fabric. The porous polymer film can include ethylene polymer, propylene polymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer, etc. polyolefin-based polymer. The porous nonwoven fabric can include glass fiber having a high melting point, polyethylene terephthalate fiber, etc. The base film 145 can have a single layer structure or a multi-layer structure including the above-described polymer film and / or nonwoven fabric.

[0131] For example, a mixed solution in which a ceramic material and a binder of the coating for the separator are mixed in a coating solvent can be coated on the base film 145 to manufacture the separator 140 provided with the ceramic coating 147 on at least one side of the base film 145.

[0132] The solvent can include, for example, tetrachloroethane, methylene chloride, chloroform, 1,1,2-trichloroethane, tetrahydrofuran, 1,4-dioxane, chlorobenzene, cyclohexanone, dimethylformamide, acetone, dimethylacetamide, dimethylsulfoxide, N-methyl-2-pyrrolidone (NMP), etc. These can be used alone or in combination with two or more.

[0133] The coating for forming the ceramic coating layer 147 can use, for example, a bar coating method, a rod coating method, a wire coating method, a comma coating method, a gravure coating method, a dip coating method, a spray coating method, a spin coating method, or the like.

[0134] According to an exemplary embodiment, the electrode assembly 150 can be formed by repeatedly disposing the positive electrode 100, the negative electrode 130, and the separator 140. In some embodiments, the electrode assembly 150 can be a winding type, a stacking type, a z-folding type, a stack-folding type.

[0135] The electrode assembly 150 can be accommodated in the case 160 together with an electrolyte, and thus a lithium secondary battery can be defined. According to an exemplary embodiment, the electrolyte can use a non-aqueous electrolyte.

[0136] The non-aqueous electrolyte can include a lithium salt and an organic solvent as an electrolyte. The lithium salt can be, for example, LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiN(CF3SO2)2, LiN(C4F9SO2)2, LiCl, LiI, or the like. + X - As an anion (X - ) of the lithium salt, F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 -, CH3CO2 - , SCN - and (CF3CF2SO2)2N - etc. These can be used alone or in combination with two or more.

[0137] The organic solvent can include an organic compound having sufficient solubility with respect to the lithium salt and the additive and having no reactivity in the secondary battery. The organic solvent can include, for example, at least one of a carbonate-based solvent, an ester-based solvent, an ether-based organic solvent, a ketone-based solvent, an alcohol-based solvent, and an aprotic solvent.

[0138] The carbonate-based solvent can include, for example, propylene carbonate (PC), ethylene carbonate (EC), butene carbonate, diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, vinylene carbonate, or the like.

[0139] The ester-based solvent can include, for example, methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (n-PA), 1,1-dimethylethyl acetate (DMEA), methyl propionate (MP), ethyl propionate (EP), fluoroethyl acetate (FEA), difluoroethyl acetate (DFEA), trifluoroethyl acetate (TFEA), γ-butyrolactone (GBL), decanolide, valerolactone, mevalonolactone, caprolactone, or the like.

[0140] The ether-based organic solvent can include, for example, dibutyl ether, tetraethylene glycol dimethyl ether (TEGDME), diethylene glycol dimethyl ether (DEGDME), dimethoxy ethane, diethoxy ethane, tetrahydrofuran (THF), 2-methyltetrahydrofuran, and the like.

[0141] The ketone-based solvent can include, for example, cyclohexanone.

[0142] The alcohol-based solvent can include, for example, ethyl alcohol, isopropyl alcohol, and the like.

[0143] The aprotic solvent can include, for example, dimethyl sulfoxide, acetonitrile, sulfolane, and propylene sulfite, and the like.

[0144] In some embodiments, the electrolyte solution can further include an additive. The additive can include, for example, a cyclic carbonate-based compound, a fluorine-substituted carbonate-based compound, a sultone-based compound, a cyclic sulfate-based compound, a cyclic sulfite-based compound, a phosphate-based compound, and a borate-based compound. These can be used alone or in combination with two or more.

[0145] The cyclic carbonate-based compound can include vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and the like.

[0146] The fluorine-substituted carbonate-based compound can include fluoroethylene carbonate (FEC), and the like.

[0147] The sultone-based compound can include 1,3-propane sultone, 1,3-propene sultone, 1,4-butane sultone, and the like.

[0148] The cyclic sulfate-based compound can include 1,2-ethylene sulfate, 1,2-propylene sulfate, and the like.

[0149] The cyclic sulfite-based compound can include ethylene sulfite, butylene sulfite, and the like.

[0150] The phosphate-based compound can include lithium difluoro bis-oxalato phosphate, lithium difluoro phosphate, and the like.

[0151] The borate-based compound can include lithium bis(oxalate) borate, and the like.

[0152] For example, the tabs (positive electrode tabs and negative electrode tabs) can respectively protrude from the positive electrode current collector 105 and the negative electrode current collector 125 and extend to one side of the case 160. The tabs can be fused together with the one side of the case 160 and connected with electrode leads (positive electrode lead 107 and negative electrode lead 127) extending to the outside of the case 160 or exposed to the outside of the case 160.

[0153] For example, the case 160 can use a pouch-type case, a prismatic case, a cylindrical case, a coin-type case, and the like.

[0154] Hereinafter, embodiments of the present application will be further described with reference to specific experimental examples. The examples and comparative examples included in the experimental examples are only for illustrating the present application and are not intended to limit the scope of the claims, and various changes and modifications can be made to the examples within the scope and technical thought of the present application, which will be obvious to those skilled in the art, and such changes and modifications are naturally included in the scope of the claims.

[0155] Examples and Comparative Examples

[0156] Comparative Example 1

[0157] (1) Manufacture of Positive Electrode

[0158] A secondary particle prepared by aggregation of primary particles (hereinafter, CAM-1) having an aspect ratio of 2.58, not doped with a doping element, and having a LiNi 0.5 Co 0.2 Mn 0.3 O2 composition was prepared.

[0159] For the aspect ratio, the cross section of the primary particle was measured using a scanning electron microscope (SEM), and the aspect ratio was calculated as the ratio of the longest diameter length to the shortest diameter length in the diameter lengths of the cross section of the primary particle.

[0160] A slurry was prepared by mixing CAM-1 as an active material, acetylene black (Denka Black) as a conductive material, and polyvinylidene fluoride (PVDF) as a binder in a weight ratio of 92:5:3. The slurry was uniformly coated on an aluminum foil having a thickness of 15 μm, and after drying at 130°C, calendered to produce a positive electrode for a lithium secondary battery.

[0161] (2) Manufacture of a negative electrode

[0162] A negative electrode slurry was prepared, which contained 90 wt% of artificial graphite as a negative electrode active material, 4 wt% of a flake type conductive material KS6 as a conductive material, 3 wt% of styrene butadiene rubber (SBR) as a binder, and 3 wt% of carboxymethyl cellulose (CMC) as a thickening agent. The negative electrode slurry was uniformly coated on a copper foil having a thickness of 15 μm, and dried and calendered to produce a negative electrode.

[0163] (3) Manufacture of a separator

[0164] A separator was produced in which a ceramic coating layer was formed on both sides of a polyethylene base film, by mixing 96 wt% of boehmite (AIO(OH)) as a ceramic material and 4 wt% of polyacrylate as a binder for the coating of a separator, and then coating on both sides of a polyethylene base film such that a ceramic coating layer of 1.5 μm was formed on each of the two sides of a polyethylene base film having a thickness of 9 μm.

[0165] (4) Manufacture of a lithium secondary battery

[0166] The positive electrode and the negative electrode produced as described above were cut to a prescribed size and stacked with the separator produced as described above interposed therebetween to constitute an electrode core, and the tab portion of the positive electrode and the tab portion of the negative electrode were respectively welded. The welded positive electrode / separator / negative electrode assembly was put into a pouch, and three faces other than the electrolyte injection face were sealed. At this time, the portion having the tabs was included in the sealing site. The electrolyte was injected through the remaining faces other than the sealing part, and the remaining faces were sealed, and then immersed for 12 hours or more to produce a lithium secondary battery.

[0167] The electrolyte used was an electrolyte in which 3 wt% of fluoroethylene carbonate (FEC), 1 wt% of 1,3-propene sultone (PRS), and 0.5 wt% of lithium bis(oxalato)borate (LiBOB) were added to a 1M LiPF6 solution prepared using a mixed solvent of EC / EMC / DEC (25 / 45 / 30: volume ratio) in an amount of 3 wt% of the total weight of the electrolyte.

[0168] After that, pre-charging was performed at a current (2.5 A) corresponding to 0.25 C for 36 minutes. After 1 hour, degassing was performed, and aging was performed for 24 hours or more, and then formation charge-discharge was performed (charge condition: CC-CV 0.2 C 4.2 V 0.05 C CUT-OFF, discharge condition: CC 0.2 C 2.5 V CUT-OFF). After that, standard charge-discharge was performed (charge condition: CC-CV 0.5 C 4.2 V 0.05 C CUT-OFF, discharge condition: CC 0.5 C 2.5 V CUT-OFF).

[0169] Examples 1 to 7 and Comparative Examples 2 to 7

[0170] A lithium secondary battery was manufactured by the same method as in Comparative Example 1, except that the composition of the positive active material, the type and content of the doping element were changed as shown in Table 1 below.

[0171] Experimental Examples

[0172] (1) Evaluation of life characteristics at normal temperature (25°C)

[0173] The lithium secondary batteries manufactured according to the examples and comparative examples were repeatedly charged (CC-CV 0.5 C 4.2 V 0.05 C CUT-OFF) and discharged (CC 0.5 C 2.75 V CUT-OFF) 500 times, and then the life characteristics at normal temperature (%) were measured by calculating the percentage (%) of the discharge capacity at the 500th time with respect to the discharge capacity at the 1st time.

[0174] Life characteristics at normal temperature (%) = (discharge capacity at the 500th time / discharge capacity at the 1st time) x 100

[0175] (2) Evaluation of power characteristics

[0176] The discharge power characteristics of the lithium secondary batteries manufactured according to the examples and comparative examples were measured using the Hybrid Pulse Power Characterization (HPPC) method according to the FreedomCar Battery Test Manual.

[0177] (3) Piercing characteristics

[0178] The lithium secondary batteries manufactured according to the examples and comparative examples were charged (1 C 4.2 V 0.1 C CUT-OFF), and then pierced with a nail having a diameter of 3 mm at a speed of 80 mm / sec, and whether or not it caught fire was evaluated.

[0179] Evaluation criteria

[0180] Fire: case where the secondary battery caught fire after being pierced

[0181] No fire: case where the secondary battery did not catch fire although it was pierced

[0182] The evaluation results are shown in Table 2 below.

[0183] [Table 1]

[0184]

[0185] [Table 2]

[0186]

[0187] Referring to Table 1 and Table 2, in Examples 1 to 7 containing the doping element, the room temperature life characteristics were 92.4% or more, the power characteristics were 2773 W / kg or more, and even if pierced with a nail, the secondary battery did not catch fire.

[0188] In Examples 2 to 6 in which the mole fraction of nickel was 0.6 to 0.94, the power characteristics were relatively improved compared to Example 1.

[0189] In Comparative Examples 1 to 7 containing no doping element, the room temperature life characteristics and the power characteristics were reduced compared to Examples in which other conditions were kept the same.

[0190] In Comparative Examples 3 to 7 in which the mole fraction of nickel was 0.7 or more, the secondary battery caught fire after being pierced with a nail.

[0191] Examples 8 to 41 and Comparative Examples 8 to 11

[0192] Lithium secondary batteries were manufactured by the same method as Comparative Example 1, except that the composition of the positive electrode active material, the type and content of the doping element, and the aspect ratio were changed as shown in Table 3 below.

[0193] The evaluation results are shown in Table 4 below.

[0194] [Table 3]

[0195]

[0196]

[0197] [Table 4]

[0198]

[0199] Referring to Table 3 and Table 4, in Examples 8 to 41 including a doping element, an aspect ratio of 1.4 to 7.0, and a content of the doping element of 100 ppm to 15,000 ppm, the room temperature life characteristics were 81.4% or more, and the power characteristics were 2,359 W / kg or more.

[0200] In Examples 13 to 41 including a doping element, an aspect ratio of 1.4 to 7.0, and a content of the doping element of 300 ppm or more, the secondary battery did not catch fire even when pierced with a nail.

[0201] Figure 3 and Figure 4 are images of a cross section of an arbitrary positive electrode active material particle among the positive electrode active material particles according to Example 18, measured using a scanning electron microscope. Referring to Figure 3 and Figure 4 It can be seen that when LiNi 0.9 Co 0.05 Mn 0.05 O2was used as primary particles, the primary particles stably aggregated to form secondary particles.

[0202] Figure 5 and Figure 6 are images of a cross section of an arbitrary positive electrode active material particle among the positive electrode active material particles according to Example 20, measured using a scanning electron microscope. Referring to Figure 5 and Figure 6 It can be seen that when LiNi 0.9 Co 0.05 Mn 0.05 O2was used as primary particles, the primary particles stably aggregated to form secondary particles.

[0203] Figure 7 and Figure 8 are images of a cross section of an arbitrary positive electrode active material particle among the positive electrode active material particles according to Example 22, measured using a scanning electron microscope. Referring to Figure 7 and Figure 8 It can be seen that when LiNi 0.9 Co 0.05 Mn 0.05 O2was used as primary particles, the primary particles stably aggregated to form secondary particles.

[0204] In Embodiments 25, 29, 30, 34, and 35, in which the aspect ratio is 2.5 to 5.5 and the content of the doping element is 2500 ppm to 12000 ppm, the room temperature life characteristics and the power characteristics are relatively improved compared to Embodiment 8.

[0205] In Comparative Examples 8 to 11, in which the doping element is not contained, the room temperature life characteristics and the power characteristics are reduced compared to Embodiments in which the other conditions are the same.

[0206] Embodiments 42 to 85

[0207] Lithium secondary batteries were manufactured by the same method as Comparative Example 1, except that the composition of the positive electrode active material, the type and content of the doping element were changed as shown in Table 5 below.

[0208] The evaluation results are shown in Table 6 below.

[0209] [Table 5]

[0210]

[0211]

[0212] [Table 6]

[0213]

[0214]

[0215] Referring to Table 5 and Table 6, in Embodiments 42 to 85 in which at least one of Al, Ti, Zr, Ba, Sr, W, Nb, Y, Mg, V, Ta, Mo, La, and B is used as the doping element and the content of the doping element is 2500 ppm to 4000 ppm, the room temperature life characteristics are 94.4% or more and the power characteristics are 2820 W / kg or more. Furthermore, even if a nail is pierced, the secondary battery does not catch fire.

[0216] In Embodiments 42 to 45, 50, 51, 58, 59, and 64 to 67, in which at least one of Ti, Zr, W, V, La, and B is used as the doping element, the room temperature life characteristics and the power characteristics are relatively improved compared to the other Embodiments.

[0217] In Embodiments 68 to 85, in which two or more doping elements are used, the room temperature life characteristics and the power characteristics are relatively improved compared to the other Embodiments.

[0218] Embodiments 86 to 96 and Comparative Examples 12 to 34

[0219] A lithium secondary battery was manufactured by the same method as Comparative Example 1, except that the composition of the positive electrode active material, the type and content of the doping element, and the thickness of the ceramic coating and the base film of the separator were changed as shown in Table 7.

[0220] The evaluation results are shown in Table 8 below.

[0221] [Table 7]

[0222]

[0223] [Table 8]

[0224]

[0225] Referring to Table 7 and Table 8, in Examples 86 to 96 containing a doping element and having a ratio of the thickness of the ceramic coating to the thickness of the separator of 0.13 to 0.44, the room temperature life characteristics were 93.5% or more, and the power characteristics were 2806 W / kg or more. In addition, even if punctured with a nail, the secondary battery did not catch fire.

[0226] In Examples 87 to 89, 92, 93, 95, and 96 having a ratio of the thickness of the ceramic coating to the thickness of the separator of 0.17 to 0.33, the room temperature life characteristics and the power characteristics were relatively improved compared to other examples.

[0227] In Comparative Examples 12 to 28 not containing a doping element, the room temperature life characteristics and the power characteristics were relatively reduced compared to other examples having the same conditions.

[0228] In Comparative Examples 12, 14 to 19, 21 to 24, and 26 to 28 not containing a doping element and having a ratio of the thickness of the ceramic coating to the thickness of the separator of 0.4 or less, the secondary battery caught fire after being punctured with a nail.

[0229] In Comparative Examples 29 to 34 containing a doping element but having a ratio of the thickness of the ceramic coating to the thickness of the separator not in the range of 0.13 to 0.44, the secondary battery caught fire after being punctured with a nail.

[0230] Examples 97 and 98

[0231] A lithium secondary battery was manufactured by the same method as Comparative Example 1, except that the composition of the positive electrode active material, the type and content of the doping element, and the position and thickness of the ceramic coating were changed as shown in Table 9.

[0232] The evaluation results are shown in Table 10 below.

[0233] [Table 9]

[0234]

[0235] [Table 10]

[0236]

[0237] Referring to Tables 9 and 10, in the embodiment in which the doped element is included and the ceramic coating layer is formed on only one side of the separator, the room temperature life characteristics are 94.6% or more, and the power characteristics are 2893 W / kg or more. Furthermore, even if a nail pierces, the secondary battery does not catch fire.

Claims

1. A lithium secondary battery comprising: a positive electrode comprising a lithium metal oxide, the lithium metal oxide including a plurality of primary particles aggregated in a form of secondary particles, and the lithium metal oxide being doped with a dopant element; a negative electrode disposed opposite to the positive electrode; and a separator disposed between the positive electrode and the negative electrode, and the separator comprising a base film and a ceramic coating layer formed on at least one side of the base film, wherein an aspect ratio of the primary particles is 1.4 to 7.0, a ratio of a thickness of the ceramic coating layer to a total thickness of the separator is 0.13 to 0.

44.

2. The lithium secondary battery according to claim 1, wherein the aspect ratio is 2.5 to 5.

5.

3. The lithium secondary battery according to claim 1, wherein the lithium metal oxide contains nickel, and a mole fraction of the nickel in a total number of moles of all elements other than lithium and oxygen in the lithium metal oxide is 0.5 or more and less than 1.

4. The lithium secondary battery according to claim 3, wherein the mole fraction of the nickel in the total number of moles of all elements other than lithium and oxygen in the lithium metal oxide is 0.6 to 0.

94.

5. The lithium secondary battery according to claim 1, wherein the dopant element includes at least one selected from the group consisting of Al, Ti, Zr, Ba, Sr, W, Nb, Y, Mg, V, Ta, Mo, La, and B.

6. The lithium secondary battery according to claim 1, wherein the dopant element includes at least one selected from the group consisting of Al, Ti, Zr, W, V, La, and B.

7. The lithium secondary battery according to claim 1, wherein the dopant element includes two or more different dopant elements.

8. The lithium secondary battery according to claim 1, wherein a content of the dopant element is 300 ppm to 15,000 ppm with respect to a total weight of the lithium metal oxide.

9. The lithium secondary battery according to claim 1, wherein a content of the dopant element is 2,500 ppm to 12,000 ppm with respect to a total weight of the lithium metal oxide.

10. The lithium secondary battery according to claim 1, wherein a ratio of a thickness of the ceramic coating layer to a total thickness of the separator is 0.17 to 0.

33.

11. The lithium secondary battery according to claim 1, wherein the total thickness of the separator is 9 μm to 18 μm.

12. The lithium secondary battery according to claim 11, wherein, the thickness of the ceramic coating layer is 2 μm to 6 μm.

13. The lithium secondary battery according to claim 1, wherein the ceramic coating layer includes a ceramic material and a binder for a coating layer of a separator.

14. The lithium secondary battery according to claim 13, wherein, the ceramic material includes at least one selected from the group consisting of alumina, titania, barium titanate, magnesium oxide, zirconia, zinc oxide, boehmite, aluminum hydroxide, magnesium hydroxide, and silica.